APPLICATION OF REPETITIVE SEQUENCE-BASED PCR ON THE RICHNESS OF VIBRIO ON THE TIGER SHRIMP (Penaeus monodon Fab.) - S arjito; Nestin E.W. Ningrum; Ocky Karna Radjasa; Slamet Budi Prayitno (JOURNAL OF COASTAL DEVELOPMENT, 2012)
A molecular-based study was conducted to estimate the richness of the Vibrio on  tiger shrimp (Penaeus monodon Fab.) from brackish water pond of Mororejo, Kendal. Tiger shrimps were collected from the extensive brackish water pond and a total of 22 isolates were obtained from hepatopancreas and telson of tiger shrimp. Based on the repetitive sequence-based polymerase chain reaction (rep-PCR), it was found that two groups of Vibrio. To investige the efectiveness of rep-PCR in estimating the richness of Vibrio on tiger shrimps, three isolates  (JTW 01, JTW 03 and JTW 06) were chosen for further investigation. On the basis of sequence analysis, the result showed  that the JTW 01, JTW 03 and JTW 06 were closely related to Vibrio sp. Absa7 clone 423.1, Vibrio splendidus and Vibrio splendidus, respectively.  The result proved that two assosiated of Vibrio on tiger shrimp were Vibrio sp. Absa7 clone 423.1 and Vibrio splendidus. Therefore  the present study highlights the effectiveness of rep-PCR in rapid grouping and estimating the richness of Vibrio on  tiger shrimp.